2009
DOI: 10.4067/s0717-97072009000100004
|View full text |Cite
|
Sign up to set email alerts
|

Study of Kinetic Formation and the Electrochemical Behavior of Polypyrrole Films

Abstract: Polypyrrole films have been electrochemically polymerized on platinum electrode under different conditions. The effect of the parameters used during the potentiostatic polymerization, such as monomer concentration, type of doping agent (i.e. counterion), deposition time (i.e. films thickness), concentration of doping agent and polymerization potential on the rate of growth and the electrochemical properties of the polymeric film has been studied. In addition, the effect of the sweep rate of polypyrrole films p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Curves show the characteristic stepped shape of the potentiostatic polymerization: After a short induction period where diffusion controls the monomer oxidation, the current increased rapidly with time, where polymer started nucleating and growing on the electrode surface. Finally, the current reached a plateau coinciding with a continuous and gradual polymer growth [ 29 30 ]. The calculated charges are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Curves show the characteristic stepped shape of the potentiostatic polymerization: After a short induction period where diffusion controls the monomer oxidation, the current increased rapidly with time, where polymer started nucleating and growing on the electrode surface. Finally, the current reached a plateau coinciding with a continuous and gradual polymer growth [ 29 30 ]. The calculated charges are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…29 The latter happens because the AOT doping anions are largely immobilized within the polymer during the oxidative polymerization due to their size and, hence, rely on cation (potassium in this case) exchange with the solution to maintain the electroneutrality of the PPy film during electrochemical modulation. 30…”
Section: Resultsmentioning
confidence: 99%
“…29 The latter happens because the AOT doping anions are largely immobilized within the polymer during the oxidative polymerization due to their size and, hence, rely on cation (potassium in this case) exchange with the solution to maintain the electroneutrality of the PPy film during electrochemical modulation. 30 The two adsorbent materials exhibited differences in hydrophobicity depending on the electrochemical signals. For PVF−PPy, when the applied potential (E) is lower than the formal potential of ferrocene (E 0 = 0.34 V versus Ag/ AgCl), the PVF−PPy adsorbent is hydrophobic; most ferrocene moieties are reduced, and organics can be taken up by reduced PVF−PPy.…”
Section: Resultsmentioning
confidence: 99%
“…The polypyrrole-pTS − film has long been known to exhibit conductivity as high as 160 S cm −1 [31]. Many studies have shown that this entrapment process is electrochemically reversible [30,32], enabling polypyrrole to act as an anion exchanger, depending upon the mobility of the entrapped counter anion [33]. Clearly, mobile anions can also be easily liberated from the polymeric film, as shown in Fig.…”
Section: Introductionmentioning
confidence: 96%